A Mobile Application for Electronic Parts Counting and Identification in Physics Laboratory - Tanaporn Leelawattananon; Suphamit Chittayasothorn (My University, 2025)
Counting of small objects such as resistors, capacitors, and inductors in physics laboratories are tedious and challenging tasks because of their numbers and small size. In this paper we present the development of a mobile application for counting and identifying small electronics parts. The system employs object edges detection using the difference of gaussian operator and classify the objects using template matching. Pictures taken using mobile phone camera are used as the input to the mobile application which correctly classify and count the objects. Electronics objects used in the counting and classification include resistors, mylar capacitors, and ceramic capacitors. The mobile application helps reduce the work required by laboratory personnel for intermediate physics laboratory management and is now deployed in the physics laboratory of the School of Science, King Mongkut's Institute of Technology Ladkrabang.
Keywords: Mobile Learning in Education; QR Code Applications and Technologies; Cloud Computing and Remote Desktop Technologies